Evolution of Telomeres in Schizosaccharomyces pombe and Its Possible Relationship to the Diversification of Telomere Binding Proteins - Sepsiova, Regina; Necasova, Ivona; Willcox, Smaranda; Prochazkova, Katarina; Gorilak, Peter; Nosek, Jozef; Hofr, Ctirad; Griffith, Jack D; Tomaska, Lubomir (PloS one, 2016)
Telomeres of nuclear chromosomes are usually composed of an array of tandemly repeated sequences that are recognized by specific Myb domain containing DNA-binding proteins (telomere-binding proteins, TBPs). Whereas in many eukaryotes the length and sequence of the telomeric repeat is relatively conserved, telomeric sequences in various yeasts are highly variable. Schizosaccharomyces pombe provides an excellent model for investigation of co-evolution of telomeres and TBPs. First, telomeric repeats of S. pombe differ from the canonical mammalian type TTAGGG sequence. Second, S. pombe telomeres exhibit a high degree of intratelomeric heterogeneity. Third, S. pombe contains all types of known TBPs (Rap1p [a version unable to bind DNA], Tay1p/Teb1p, and Taz1p) that are employed by various yeast species to protect their telomeres. With the aim of reconstructing evolutionary paths leading to a separation of roles between Teb1p and Taz1p, we performed a comparative analysis of the DNA-binding properties of both proteins using combined qualitative and quantitative biochemical approaches. Visualization of DNA-protein complexes by electron microscopy revealed qualitative differences of binding of Teb1p and Taz1p to mammalian type and fission yeast telomeres. Fluorescence anisotropy analysis quantified the binding affinity of Teb1p and Taz1p to three different DNA substrates. Additionally, we carried out electrophoretic mobility shift assays using mammalian type telomeres and native substrates (telomeric repeats, histone-box sequences) as well as their mutated versions. We observed relative DNA sequence binding flexibility of Taz1p and higher binding stringency of Teb1p when both proteins were compared directly to each other. These properties may have driven replacement of Teb1p by Taz1p as the TBP in fission yeast.
Keywords: DNA vazebné proteiny; Animals; Base Sequence; Oligonucleotides; oligonukleotidy; transkripční faktory; Microscopy, Electron; Fluorescence Polarization; retardační test; fluorescenční polarizace; vazba proteinů; telomery; lidé; Telomere; Transcription Factors; Evolution, Molecular; molekulární evoluce; elektronová mikroskopie; Telomere-Binding Proteins; Genetic Variation; Phylogeny; proteiny vázající telomery; Schizosaccharomyces pombe - proteiny; sekvence nukleotidů; Schizosaccharomyces; DNA-Binding Proteins; zvířata; Schizosaccharomyces pombe Proteins; fylogeneze; genetická variace; Electrophoretic Mobility Shift Assay; Protein Binding; Humans